2016
DOI: 10.1038/bonekey.2016.86
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic augmentation of the osteoporotic proximal femur—mission impossible?

Abstract: The high incidence of secondary hip fractures and the associated markedly increased mortality call for preventive actions that could help to avoid these injuries. By providing immediate strengthening and not relying on patient compliance, internal prophylactic augmentation of the osteoporotic proximal femur may overcome the main limitations of systemic bone drugs and wearable protective pads. However, such a method would have to provide sufficient and reliable strengthening effect with minimal risks and side e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…Previous efforts to prevent hip fractures using mechanical methods, reviewed in Varga et al, included prophylactic pinning with metal implants or a PEEK rod system, and injecting silicone rubber or PMMA . The metal systems in general failed to improve biomechanical properties and introduced concerns about stress risers . Using silicone rubber to fill the proximal femur failed to improve biomechanics .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous efforts to prevent hip fractures using mechanical methods, reviewed in Varga et al, included prophylactic pinning with metal implants or a PEEK rod system, and injecting silicone rubber or PMMA . The metal systems in general failed to improve biomechanical properties and introduced concerns about stress risers . Using silicone rubber to fill the proximal femur failed to improve biomechanics .…”
Section: Discussionmentioning
confidence: 99%
“…In the osteoporotic femurs in this study, only 28% (7/25) of control femurs had a failure load greater than 2,900 N whereas 72% (18 of 25) of treated femurs exceeded the "fragile bone strength" threshold of 2,900 N. These data infer that the positive strength increment observed immediately after implant injection is likely to be clinically important and has the potential to reduce fracture risk. Previous efforts to prevent hip fractures using mechanical methods, reviewed in Varga et al, 38 included prophylactic pinning with metal implants 27,39 or a PEEK rod system, 20,26 and injecting silicone rubber 24,25 or PMMA. 19,[21][22][23]40 The metal systems in general failed to improve biomechanical properties and introduced concerns about stress risers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with a recent hip fracture, the risk of a second contralateral hip fracture is significantly elevated in the months after the first fracture, and remains elevated for years [13]. There is a growing global consensus among leading clinicians that minimally-invasive surgical approaches intended to complement current therapies warrant consideration to further reduce risk of fragility fracture in patients at elevated risk [11,14]. The recently published guidance on diagnosis and management of postmenopausal osteoporosis in women by the International Osteoporosis Foundation (IOF) and European Society of Clinical and Economic Aspects of Osteoporosis (ESCEO) included a local osteo-enhancement procedure (LOEP) as a treatment option [15].…”
Section: Introductionmentioning
confidence: 99%
“…only 31% of included patients returned to their pre-injury walking ability. To address the issue of hip fragility fracture prevention, a new medical device, Y-STRUT ® (Hyprevention, France), was developed to be implemented in the proximal femur by minimally invasive surgery [22,23]. Biomechanical tests on human osteoporotic femurs showed that the implantable medical device, placed in the proximal femur, increases the bone fracture load and energy to fracture in case of fall without modifying or worsening the nature of the fracture [24].…”
Section: Introductionmentioning
confidence: 99%